Against reason : Schopenhauer, Beckett, and the aesthetics of irreducibility - McGrath, Anthony (Trinity College (Dublin, Ireland). School of English, 2015)
This dissertation examines the relationship between the philosophy of Schopenhauer and the forms and themes of Beckett’s critical and creative writings. My research aims to show that Beckett’s aesthetic preoccupations are consonant with some of Schopenhauer’s seminal arguments regarding the arational basis of artistic composition and appreciation and the impotence of reason in human affairs. While Beckett’s critical writings are, in places, formidably opaque, this study explores the ways in which such texts can be elucidated when their intertextual affinities with Schopenhauer’s arguments are revealed. Using Schopenhauer’s thought as my presiding interpretative framework, I propose to demonstrate that the widespread presence of philosophical and theological ideas in Beckett’s creative work signifies less about his personal convictions that it does about his authorial aims. In this sense, I highlight the ways in which discursive ideas were appropriated and manipulated by Beckett for literary ends.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin